Using Virtual Reality During Chemotherapy to Support Emotional Regulation in Patients: Adding an Olfactory Reinforcement or Not? - Hélène Buche; Aude Michel; Nathalie Blanc (Virtual Worlds, 2025)
Introduction: In line with previous research conducted during chemotherapy to explore whether virtual reality (VR) can support patients’ emotional regulation, this study examines the relevance of adding olfactory reinforcement to VR sessions during breast cancer treatment. Methods: An experimental protocol assessed the impact of VR sensoriality in 50 patients over three chemotherapy sessions. Each patient experienced a 10-min immersion in a natural environment under three randomized conditions: Contemplative VR, Participatory VR, Participatory VR with olfactory reinforcement. The sense of presence measured immersion, while anxiety, depression, and emotional state were evaluated using a within-subject design to compare the effects of each VR modality. Results: A reduction in anxiety and depression was observed in patients regardless of the type of VR immersion experienced. The interactive and multimodal nature of VR may support patients in their emotional regulation. Conclusions: This study provides preliminary evidence for the usefulness of olfactory enhancement in VR during chemotherapy sessions in breast cancer patients. The multimodal potential of VR contributes to the reduction of anxiety and depression by inducing a positive emotional experience in a soothing natural environment. The reported results highlight the value of sensorimotor VR, which also stimulates the sense of smell, in improving supportive care.